2020
DOI: 10.1016/j.biopsych.2019.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Recent Efforts to Dissect the Genetic Basis of Alcohol Use and Abuse

Abstract: Alcohol use disorders (AUD) are defined by several symptom criteria, which can be further dissected at the genetic level. Over the past several years, our understanding of the genetic factors influencing alcohol use and abuse has progressed tremendously; hundreds of loci have now been implicated in different aspects of alcohol use. Previously known associations with alcohol metabolizing enzymes (ADH1B, ALDH2) have been definitively replicated. Additionally, novel associations with loci containing the genes KLB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 79 publications
7
64
0
Order By: Relevance
“…Only the RISK PC and GSCAN DPW PRS were associated with AUD criteria in FT12. Overall, the unique contributions of each PRS reinforce the notion that the genetics of AUD are multifaceted, comprised of risk for level of consumption, alcohol-related problems, and behavioral disinhibition 31,32 . Evaluating the AUC for the combined PRS revealed the combined effect of PRSs only marginally improved the AUC, similar to recent analyses for coronary artery disease 33 and ischemic stroke 34 .…”
Section: Discussionmentioning
confidence: 65%
“…Only the RISK PC and GSCAN DPW PRS were associated with AUD criteria in FT12. Overall, the unique contributions of each PRS reinforce the notion that the genetics of AUD are multifaceted, comprised of risk for level of consumption, alcohol-related problems, and behavioral disinhibition 31,32 . Evaluating the AUC for the combined PRS revealed the combined effect of PRSs only marginally improved the AUC, similar to recent analyses for coronary artery disease 33 and ischemic stroke 34 .…”
Section: Discussionmentioning
confidence: 65%
“…Thus, two individuals could receive the same diagnosis but not share any common symptoms. As Sanchez-Roige et al [ 18 ] note, a diagnosis of AUD represents the end point of a series of stages that includes (1) initial sensitivity to the effects of alcohol, (2) the transition to hazardous alcohol use and the loss of control over alcohol-seeking and alcohol-taking, (3) the development of tolerance, and (4) relapse. Each of these domains is likely to be influenced by unique and perhaps non-overlapping networks of genes.…”
Section: Introductionmentioning
confidence: 99%
“…Genetics are a substantial etiological factor influencing ethanol use and AUD (Agrawal & Lynskey, 2008;Enoch & Goldman, 2001;Heath et al, 1991Heath et al, , 1997Prescott et al, 1999;Reed et al, 1994;Swan et al, 1990;Verhulst et al, 2015a), with influences on traits that moderate onset of drinking and both quantity and patterns of drinking that may themselves predict risk of developing AUD (Chassin et al, 2002;Dash et al, 2020;Geels et al, 2012;Kalmus, 1967;McGue et al, 2001). While ethanol consumption and AUD may possess partially distinct genetic architecture (Sanchez-Roige et al, 2020), observed genetic correlations between these traits suggest that genetic factors affecting consumption may reveal factors that affect AUD risk (Kranzler et al, 2019). However, the genes/gene networks implicated in traits that influence drinking patterns and the variants that drive their variation to potentially affect AUD vulnerability are largely undiscovered (Verhulst et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%